Nutrient composition of meals served to adult inpatients in public hospitals in North West, South Africa - Mantombi J. Jiyana; Lindiwe J. Ncube (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: A high-quality meal is essential to patients’ food enjoyment and nutritional value. Patients’ health and nutritional status depend on the quality of meals provided by the hospital food service providers. Equally, patients are largely inactive and could experience energy imbalances if the ‘energy in’ exceeds the ‘energy out’, increasing the chances of the inception of obesity and obesity-related illnesses.